Analisis Perbandingan Kinerja Badan Penanaman Modal serta Pengaruh PMA dan PMDN terhadap Pertumbuhan Ekonomi di Indonesia - Fajri Ardiansyah; Suhairi Suhairi; Nini Syofri Yeni (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This research aimed to know comparative Regional Board of Investment Performance in Indonesia and examined effect of foreign and domestic investment on economic growth. Sample used in this research is 34 Board of Investment and Integrated Licensing (BPMPTSP) of the provinces in Indonesia in 2015-2018 that determined by purposive sampling method. Data used is secondary data of target and realization of foreign and domestic investment from BKPM and PDRB rate from BPS. Data analysis technique used is average of total realization of investment, average growth per year of investment (CAGR ratio), average ratio of investment target achievement (Effectiveness ratio). To examined effect of investment on economic growth used data panel regression analysis. Result of average of total realization of investment analysis show that West Java Province has best performance on foreign investment, while East Java as the best province on average realization of direct investment. West Sulawesi Province has the best performance measured by average growth of foreign investment, while Maluku is a province with best performance based on ratio of average growth of domestic investment. Analysis of target achievement that used effectiveness ratio show that North Sulawesi has the best performance on achieved the investment target. F- test result show that simultaneously there are significant effect between foreign and domestic investment on economic growth. Based on t-test result, partially there are significant effect between foreign and domestic investment on economic growth.